Developing a data-driven approach to optimizing pharmacy inventory management - Anand Das Vaishnav, Venu; Patel, Ritesh (Journal of Neonatal Surgery, 2025)
The stock of products, commodities, or other financial resources that are kept or set aside for future production or to satisfy future demand is known as inventory. For example, inventory can include raw materials that are awaiting use in the creation of items, finished goods that are awaiting shipping from the factory, wholesaler, or retailer, and semi-finished or in-process goods that are temporarily held throughout the production process. Equipment, furnishings, fittings, etc. are also included in inventory. Direct and indirect inventories are two categories under which the term inventory can be separated. Items that directly contribute to the manufacturing process and are a necessary component of final goods are included in direct inventories. Raw materials, work-in-progress, and finished commodities are the three categories into which direct inventories can be divided. Items that are required for manufacturing but do not end up in the final product, such as lubricants, grease, oil, gasoline, office supplies, maintenance supplies, etc., are included in indirect inventories. Although there are many reasons why inventories are kept, they generally serve the following fundamental purposes.